Intelligent Virtual Environment in STEM Education: A Systematic Literature Review for Sustainable Digital Learning - Alhusni, Hanan Zaki; Prahani, Binar Kurnia; Jatmiko, Budi; Hulu, Noval Maleakhi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to analyze the development and application of Intelligent Virtual Environment (IVE) in STEM education to support sustainable digital learning. The study focuses on identifying research trends, technologies used, and the impact of immersive digital environments on STEM learning outcomes. Method: This research employed a Systematic Literature Review (SLR) approach to synthesize relevant studies published in the last five years. Articles were collected from several academic databases, including Scopus, Web of Science, ScienceDirect, IEEE Xplore, and Google Scholar. The selection process followed the PRISMA framework to ensure systematic identification, screening, eligibility assessment, and inclusion of relevant studies. A total of 15 articles were selected based on inclusion criteria related to immersive technologies, artificial intelligence, and virtual learning environments in STEM education. The selected studies were analyzed to identify research trends, technological approaches, and reported learning outcomes. Result: The results show that Intelligent Virtual Environment technologies, particularly those integrating virtual reality, augmented reality, and artificial intelligence, have been widely applied in STEM learning. These technologies improve conceptual understanding, student engagement, and interactive learning experiences. The findings also indicate that immersive learning environments support visualization of complex scientific concepts and encourage active learning through simulation and exploration. Novelty: This study provides a comprehensive synthesis of recent research on Intelligent Virtual Environment in STEM education and highlights its role in advancing sustainable digital learning. The review also identifies current research trends and future research directions for integrating immersive technologies and artificial intelligence in STEM education.